Mentor teachers’ perceptions about their ability to teach geography through interactive whiteboards - Kolnik, Karmen (Journal for Geography, 2012)
In this paper we present some of the trends of introducing interactive whiteboards in teaching geography in terms of both the comparison of Slovenian schools equipped with interactive whiteboard signs as their availability and actual involvement in teaching geography. The opinions of students mentor teachers in geography teaching practice, who participated in a short pilot qualitative survey, showed how they assess their current skills of teaching geography using the interactive whiteboards and what their experiences are. Collected opinions suggest that the surveyed teachers of geography are according to the five-step scale of the process of learning strategies using interactive tablets (Hooper in Rieber 1995) at the beginning: the familiarization phase and phase of use. Only individuals are reaching the level of integration: everyday usage of the interactive whiteboard, which became their way of everyday teaching. But no one expressed the view that they are developing new teaching strategies (5th step), which are based on their personal knowledge and experiences that are adjusted to the diverse individual needs of students.